El joven Karl Marx : filosofía alemana, política moderna y realización humana - Leopold, David; Blasco Castiñeyra, Jaime; Leopold, David (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2012)
This text presents a study of Karl Marx's early writings. They provide the fascinating spectacle of a powerful and imaginative intellect wrestling with complex and significant issues, but they also present formidable interpretative obstacles to modern readers.
Includes bibliographical references.
Text in German and Spanish.
Online resource; title from ePub title page (Digitalia, viewed March 8, 2017)
Keywords: Marx, Karl, -- 1818-1883.; Communism; Philosophy, Marxist; Philosophy, German; Electronic books